Dinamika Kemiskinan pada Masyarakat Melayu di Pulau Karas: Sebuah Analisis dari Presfektif Teologi Islam - Sinta Dewi, Ning Ratna (Abrahamic Religions: Jurnal Studi Agama-Agama, 2023)
Karas Island is one of the islands in the Riau Archipelago, which is inhabited by the Malay tribe with the livelihood of almost all family heads working as fishermen. The Malay tribe as it is known is the largest tribe in Indonesia. History records that almost all corners of Indonesia are inhabited by ethnic Malays. The special features of the Malay tribe are mainly their customs which are characterized by the Islamic religion, as well as the use of Malay Arabic script/language which is applied in schools and to this day there are still several schools that teach Malay Arabic lessons, especially in the Riau and Riau islands. The existence of Malay traditional clothing which is mandatory at school and also in government agencies is still maintained today. Although the Malays have their privileges, at this time the Malays are not as grand as they used to be. Many Malay people currently live in poverty and most live on the sea coast and rely on the sea as a source of life. This can be seen in the development of the Malay ethnic group in the Riau Archipelago, to be precise on Karas Island, which is the object of this research study. This research method is field research (field research) using a qualitative approach with the stages of observation, documentation and interviews. The aim of this research is to find out the pattern of life of the people on Karas Island from a theological perspective and what will be connected to the poverty that exists in that place using qualitative research methods which will later get accurate results directly from the Malay community on Karas Island.AbstrakPulau Karas merupakan salah satu pulau yang terdapat di Kepulauan Riau, yang dihuni oleh suku Melayu dengan mata pencaharian hampir semua kepala keluarga berprofesi sebagai nelayan. Suku Melayu sebagaimana yang dikenal merupakan suku terbesar yang ada di Indonesia. Sejarah mencatat bahwa hampir seluruh penjuru Indonesia di diami oleh suku Melayu. Keistimewaan dari suku Melayu terutama pada adat istiadatnya yang bercirikan agama Islam, serta penggunaan aksara/bahasa Arab Melayu yang diterapkan di sekolah-sekolah dan hingga saat ini masih ada beberapa sekolah yang mengajarkan pelajaran Arab Melayu terutama di kepulauan Riau dan Riau. Eksistensi pakaian adat Melayu yang menjadi pakaian wajib di sekolah dan juga instansi pemerintahan masih dipertahankan hingga saat ini. Meskipun suku Melayu memiliki keistimewaan, namun pada saat ini suku Melayu lah yang tidak semegah dahulu. Masyarakat Melayu saat ini banyak yang hidup dalam kemiskinan dan sebagian besar bertempat tinggal di pesisir laut dengan mengandalkan laut sebagai sumber kehidupan. Hal ini nampak pada perkembangan suku Melayu yang ada di Kepulauan Riau, tepatnya di Pulau Karas yang menjadi objek dari kajian penelitian ini. Metode penelitian ini penelitian lapangan (field research) menggunakan pendekaan kualitatif dengan  tahap observasi, dokumentasi dan wawancara. Tujuan Peneltian ini untuk mengetahui pola kehidupan masyarakat di Pulau Karas dalam kacamata teologi dan yang akan dihubungkan dengan kemiskinan yang ada di tempat tersebut dengan menggunakan metode penelitian kualitatif yang nantinya akan mendapatkan hasil yang akurat langsung dari masyarakat Melayu yang ada di Pulau Karas.